Health Among the Elderly in Germany New Evidence on Disease, Disability and Care Need - Doblhammer, Gabriele (Beitrage zur Bevölkerungswissenschaft, 2014)
Whether increasing life expectancy leads to better health remains still controversial. Three topics are explored: (1) vanguard groups which inform about possible levels of health if the general social and environmental conditions were to approach those of the vanguard group; (2) the social and behavioral determinants of health differentiated into proximal and distal factors; (3) vulnerable groups such as migrants and the health differences between migrant groups. Newly available population-based data as well as new study designs and advanced statistical modelling form the basis for the empirical analyses.